Quorum sensing gene regulation in Staphylococcus epidermidis reduces the attraction of Aedes aegypti (L.) (Diptera: Culicidae) - Kim, Dongmin; Crippen, Tawni L.; Jordan, Heather R.; Tomberlin, Jeffery K. (Frontiers in Microbiology, 2023)
Identifying mechanisms regulating mosquito attraction to hosts is key for suppressing pathogen transmission. Historically, the ecology of the host microbial community and its influence on mosquito attraction have not been extensively considered. Behavioral choice assays were applied along with volatile collection followed by GC-MS and RNA transcriptome analyses of bacteria with and without a quorum sensing inhibitor. Utilizing the quorum sensing inhibitor furanone C-30 on a skin-inhabiting bacterium, Staphylococcus epidermidis, we disrupted its interkingdom communication with adult Aedes aegypti, and mitigated their attraction to a blood-meal by 55.1%. One potential mechanism suppressing mosquito attraction could be the reduction (31.6% in our study) of volatiles and associated concentrations from the bacteria by shifting S. epidermidis metabolic (12 of 29 upregulated genes) and stress (5 of 36 downregulated genes) responses. Manipulating quorum sensing pathways could serve as a mechanism to reduce mosquito attraction to a host. Such manipulations could be developed into novel control methods for pathogen-transmitting arthropods other than mosquitoes.